Moment redistribution on continuous reinforced concrete beams - Goh, Shi Yi. (2010)
The increasing use of high strength steel and concrete, together with highly efficient and accurate programs, engineers are now able to design and satisfy the ultimate limit states of any concrete structure with more slender sections. Serviceability requirements such as cracking and deflections of concrete structures have increasingly become an important factor to consider. Cracks propagations are highly load-dependent and they have significant effects on the flexural stiffness and thus, the deflections of the member. with an increase in the moment values on the sections of a member, the flexural stiffness decreases which in turn cause an increase in the deflection.